Kontrol Keluarga terhadap Pencegahan Kenakalan Remaja - Natasya, Sarah Rodia; Ruslan, Ruslan; Sanusi, Sanusi (Universitas Negeri Semarang, 2021)
Adolescence is a turn in adolescents who are very vulnerable to the emergence of a problem that is the most important in juvenile delinquency. It takes special attention and a good understanding and proper explanation of the problem. This research is a research that belongs to the type of descriptive research with a qualitative approach, the data collection instrument uses in-depth interviews to obtain data in the field, the conclusion of this study is that juvenile delinquency occurs due to the absence of supervision and attention from parents as well as the environment towards children's growth, and the lack of inculcation of religious values in the environment in which the children grow and develop. Suggestions from this study are that parents must be role models, and have good attitudes towards children, motivate children, as well as provide directions with whom and which community where youth can make friends and get along. Parents strive to produce a harmonious, communicative, and safe family for the teenagers themselves, helping them to be able and smart in choosing friends and a good environment. Also provides a positive activity that makes teenagers feel comfortable in the community.